If the condom fits, wear it: a qualitative study of young African-American men. Issue 4 (4th August 2004) - Crosby, R A; Graham, C A; Yarber, W L; Sanders, S A
Abstract : Objective: To extend the current knowledge base pertaining to condom failure among young African-American men by assessing their experiences with male condom use. Methods: Qualitative assessments were conducted with 19 African-American men (aged 18–29 years) who had just been diagnosed with an STI and reported using condoms in the previous 3 months. Results: Five categories were identified from the data. These categories pertained to: (1) the "fit and feel" of condoms; (2) condom brand and size; (3) application problems; (4) availability of condoms and lubricants; and (5) commitment to condom use. Common themes included reasons why men believed condoms would break or slip off during sex. Comfort problems, including tightly fitting condoms and condoms drying out during intercourse, were mentioned frequently. Condom associated erection problems were often described. Many men also noted that condom use reduced the level of sexual satisfaction for their female partners. Men noted that finding the right kind of condom was not always easy and it became apparent during the interviews that men typically did not acquire lubrication to add to condoms. Despite their expressed problems with using condoms, men were, none the less, typically emphatic that condom use is an important part of their protective behaviour against STIs. Conclusion: Men were highly motivated to use condoms; however, they experienced a broad range of problems with condom use. With the exception of losing the sensation of skin to skin contact, the vast majority of these problems may be amenable to behavioural interventions.